Peripheral Blood-Derived Mesenchymal Stem Cells: Growth Factor-Free Isolation, Molecular Characterization and Differentiation - Noushin Pouryazdanpanah; Shahriar Dabiri; Ali Derakhshani; Reza Vahidi; Alireza Farsinejad (Iranian Society of Pathology, 2018)
Background and Objectives: The mesenchymal stem cells derived from peripheral blood (PB) have been recognized as a promising source for allogeneic cell therapy. The aim of this study was to investigate the isolation, growth and differentiation ability of peripheral blood-isolated mesenchymal stem cells. Methods: The mononuclear cells were purified from fresh peripheral blood using density gradient centrifugation then cultured in a suitable medium, expanded and characterized. In the following, these cells were cultured in specific adipogenic and osteogenic differentiation media.Results and Conclusion: In spite of the absence of any stimulating factor, the cells adhered to the flasks and developed a rather homogeneous, spindle-shaped morphology after consecutive passages. The cells were confirmed to have mesenchymal phenotype by expression of specific markers (CD90, CD105, and CD73) and absence of CD45 marker, which is specific for hematopoietic stem cells. They could differentiate into lineage-specific committed cells (osteoblasts and adipocytes). According to the findings, the conventional, labour-intensive and time-consuming approaches are not necessary to obtain an optimal number of cells from peripheral blood. This relatively accessible and minimally invasive source of stem cells may open a new era for practical exploitation in regenerative medicine.